If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(6 + x) = 34 (6 * 2 + x * 2) = 34 (12 + 2x) = 34 Solving 12 + 2x = 34 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 2x = 34 + -12 Combine like terms: 12 + -12 = 0 0 + 2x = 34 + -12 2x = 34 + -12 Combine like terms: 34 + -12 = 22 2x = 22 Divide each side by '2'. x = 11 Simplifying x = 11
| 4x^6+16x^5+42x^4=0 | | -0.6y-9.3=1.206 | | 2x+x+50+x+x+20=360 | | X-(-20)=7 | | 22=-16x^2+40x | | 135+147+103+90+118+2x=360 | | X+(-7)=9 | | 2x-10+x+30+70=180 | | X^2-11.5x+32.5=0 | | (-6-6i)-(5+i)= | | X+3=2*x | | 3(b+1)=4b-2(-3) | | 2x-7/x=x-2/5 | | 0.05(5-7x)=8-(4x+6) | | (3x+2)(4x^2-5x-3)= | | (4x+35)= | | 24=x/1 | | 27a^12= | | 49p^4-84p^2+36=0 | | x+3(x+2)=2(x+1)+20 | | 13x-3x=-60 | | P=(20+05x)+0.15(20+0.5x) | | 15=-3(3+4) | | f(x)=cos(7x+5) | | 0.2a+9=11.4 | | Cos((pi/3)/x) | | y-80=1.357(x-0) | | (4x+3y+1)dx+(x+y+1)dy=0 | | 5c/6-c/6 | | (D^6+1)y=0 | | h=-16t^2+224t+1152 | | V-7b=3 |